Waiter’s Communication Abilities at Some Cafes on Jimbaran Beach - Pastini Ni Wayan; Susianti Hartanti Woro; Ariasri Nyoman Reni (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2023)
The research endeavors to examine the utilization of the English language by waitress operating within the Jim-baran Beach tourist precinct in Bali. The primary objec-tive is to evaluate the proficiency of their English commu-nication skills and ascertain the repercussions on custom-er encounters and the advancement of the local tourism sector. The investigation seeks to delve into the extent to which waitress in Jimbaran Beach can effectively engage with international patrons in English. Employing a qualita-tive descriptive methodology, this study analyzes the Eng-lish communication practices of waitress across diverse cafes situated in the Jimbaran Beach tourism vicinity. Da-ta is gathered through firsthand field observations and interviews with the waitress. The findings of the research unveil the presence of recurrent language errors in the English communication employed by the waitress. These errors encompass grammatical inaccuracies that involve both superfluous additions and inadvertent omissions of words. The study underscores the paramount importance of enhancing the English language aptitude of the wait-ress, particularly when serving overseas tourists. Drawing from these research findings, the proposal of regular training sessions targeted at refining the grasp of English grammar among Jimbaran Beach waitress emerges. The overarching objective is to cultivate a more fluid and pre-cise English communication proficiency among the wait-ress within the Jimbaran Beach precinct, thereby ensuring a positive encounter for tourists and contributing to the advancement of tourism while concurrently augmenting the favorable perception of the destination